The cracked mirror : an Indian debate on experience and theory - Gopal Guru (Oxford, 2012)
"This volume explores the relationship between experience and theory in Indian social sciences in the form of a dialogue. It focuses on questions of Dalit experience and untouchability. While Gopal Guru argues that only those who have lived lives as subalterns can represent them accurately, Sundar Sarukkai feels that people located outside the community can also represent them. Thematically divided into five sections, the first discusses the problems associated with theory in the social sciences in the Indian context. The next makes inquiries into the nature of personal and collective experience. The third explores the larger connection between ethics and theory in India, both in the natural and social sciences. The fourth examines the ontological and epistemological nature of experience itself and the politics of experience, and the last focuses on the experience and theory of experience in India. The authors invoke the image of a cracked mirror to suggest a more complex and distorted relation between experience and theory."--Publisher's website.